Association of Fasting Lipid Profile with Insulin Resistance in Non-Alcoholic Fatty Liver Disease Patients - Hussain, Farhad; Aziz, Rehana; Karmakar, Pijush; Chowdhury, Md Hasan Murad; Hoque, Asma; Aktar, Fahmida (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Back ground: Non-Alcoholic Fatty Liver Disease (NAFLD) is a common cause of Chronic Liver Disease (CLD) worldwide and is becoming a major public health problem. NAFLD has been recognized as a hepatic manifestation of Metabolic Syndrome (MetS) linked with Insulin Resistance (IR) and is currently considered as the hepatic component of the Metabolic Syndrome (MetS). NAFLD is strongly associated with IR and is mostly silent which is often discovered incidentally through elevated hepatic enzyme levels. The purpose of this study is to find out the association of Fasting Lipid Profile (FLP) with IR in NAFLD subjects. Materials and methods: A prospective hospital based cross sectional study was carried out in the Department Of Biochemistry, Institute of Nuclear Medicine and Allied Sciences (INMAS) and Chittagong Medical College Hospital. One hundred & fifty (150) subjects aging between 18-60 years were included in this study by non probability consecutive sampling method. Important variables in this study were Fasting Plasma Glucose (FPG) Fasting Serum Insulin (FPI) and Fasting Lipid Profile (FLP). IR was calculated by using Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) index i.e. (FPI μIU x FPG mmol/L)/22.5. Results: In this study HOMA-IR was significantly higher in cases than that of controls (4.77±0.16) and showing Insulin Resistance (IR) in 90% of the cases. There was a significant association of HOMA-IR with increased serum Triglyceride (TG) in NAFLD cases. Conclusion: The findings of the current study suggest that independent variable such as increased Serum TG was associated with IR in NAFLD subjects. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 3-7